Psychological Distress and Anxiety Levels Among Health Care Workers at the Height of the COVID-19 Pandemic in the United Arab Emirates - Basema Saddik; Basema Saddik; Iffat Elbarazi; Mohamad-Hani Temsah; Mohamad-Hani Temsah; Fatemeh Saheb Sharif-Askari; Waad Kheder; Amal Hussein; Hellme Najim; Riyad Bendardaf; Riyad Bendardaf; Qutayba Hamid; et al. (Frontiers Media S.A., 2021)
Objectives: Providing medical care during a global pandemic exposes healthcare workers (HCW) to a high level of risk, causing anxiety and stress. This study aimed to assess the prevalence of anxiety and psychological distress among HCWs during COVID-19.Methods: We invited HCWs from 3 hospitals across the United Arab Emirates (UAE) to participate in an anonymous online survey between April 19-May 3, 2020. The GAD-7 and K10 measures were used to assess anxiety and psychological distress. Logistic regression models assessed associations between knowledge, attitude, worry, and levels of anxiety and psychological distress.Results: A total of 481 HCWs participated in this study. The majority of HCWs were female (73.6%) and aged 25-34 years (52.6%). More than half were nurses (55.7%) and had good knowledge of COVID-19 (86.3%). Over a third (37%) of HCWs reported moderate/severe psychological distress in the K10 measure and moderate/severe anxiety (32.3%) in the GAD-7, with frontline workers significantly reporting higher levels of anxiety (36%). Knowledge of COVID-19 did not predict anxiety and psychological distress, however, HCWs who believed COVID-19 was difficult to treat and those who perceived they were at high risk of infection had worse mental health outcomes. Worry about spreading COVID-19 to family, being isolated, contracting COVID-19 and feeling stigmatized had 1.8- to 2.5-fold increased odds of symptoms of mental health problems. Additionally, HCWs who felt the need for psychological support through their workplace showed increased odds of psychological distress.Conclusion: HCWs in the UAE reported a high prevalence of psychological distress and anxiety while responding to the challenges of COVID-19. The findings from this study emphasize the public, emotional and mental health burden of COVID-19 and highlight the importance for health systems to implement, monitor, and update preventive policies to protect HCWs from contracting the virus while also providing psychological support in the workplace.